Transdisciplinary Epistemic Practices as a Teaching Narrative: Redesigning a Library and Information Science course that integrates STEM, Arts, and Design - Bowler, Leanne; Rosin, Mark (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
This article reports on revisions to a course in Library and Information Science (LIS) made by the instructor, to apply, test, and evolve a transdisciplinary approach to class inquiry. This study was part of a larger research project grounded in the Scholarship of Teaching and Learning, entitled Exploring Transdisciplinary Approaches to STEM Teaching and Learning, whose purpose was to support transdisciplinary educators in justifying, evaluating, and legitimizing knowledge claims about their work through the application of a novel Transdisciplinary Epistemic Practices(TEP) model integrating elements from STEM, Arts, and Design (often referred to as STEAM). The TEP model is a conceptual tool that promises to be useful for the Critical Making stances that are common in technology courses for librarians. It was operationalized and tested in eleven courses across Pratt Institute, including a Library and Information Science course called Growing Up Digital (INFO 678), which is the focus of this paper. The first author, Leanne Bowler, was a participant in the study, applying action research methods to her own teaching practices in this class, and reporting results back to the larger project led by Mark Rosin.